Eksplorasi Ruang Lingkup Penelitian Kebahasaan - Safina Salma Sa’adah; Ubaid Ridlo; Maudlotun Nisa (Simpati, 2024)
This study aims to review the scope of linguistic research, highlighting the various branches and approaches used in the study of language. Linguistic research is a multidisciplinary field that includes the analysis of language structure, use, and its role in society. In this paper, we discuss some of the main branches of theoretical linguistics, including phonology, morphology, syntax, semantics, and pragmatics. In addition, we also explore applied linguistics which involves the application of linguistic theory in practical contexts such as language education, translation, and language technology. Interdisciplinary approaches in linguistic research, which combine perspectives from psychology, anthropology, and computer science, are also a major focus of this study. We highlight the importance of appropriate methodology in linguistic research, including qualitative and quantitative methods, as well as the use of modern analytical tools such as linguistic software and natural language processing techniques. The results of this study indicate that a comprehensive understanding of the scope of linguistic research can make a significant contribution to the development of linguistics and its applications in various fields. These findings are expected to provide insights for researchers, practitioners, and educators in designing more effective language studies and teaching programs.